CircFAT1 Promotes Cancer Stemness and Immune Evasion by Promoting STAT3 Activation. Issue 13 (2nd May 2021) - Jia, Lingfei; Wang, Yilun; Wang, Cun‐Yu
Abstract: Cancer stemness and immune evasion are closely associated, and play critical roles in tumor development and resistance to immunotherapy. However, little is known about the underlying molecular mechanisms that coordinate this association. Here, it is reported that elevated circular RNA FAT1 (circFAT1) in squamous cell carcinoma (SCC) unifies and regulates the positive association between cancer stemness and immune evasion by promoting STAT3 activation. circFAT1 knockdown (KD) reduces tumorsphere formation of SCC cells in vitro and tumor growth in vivo. Bioinformatic analysis reveals that circFAT1 KD impairs the cancer stemness signature and activates tumor cell‐intrinsic immunity. Mechanistically, circFAT1 binding to STAT3 in the cytoplasm prevents STAT3 dephosphorylation by SHP1 and promotes STAT3 activation, resulting in inhibition of STAT1‐mediated transcription. Moreover, circFAT1 KD significantly enhances PD1 blockade immunotherapy by promoting CD8 + cell infiltration into tumor microenvironment. Taken together, the results demonstrate that circFAT1 is an important regulator of cancer stemness and antitumor immunity. Abstract : Cancer stemness and immune evasion are tightly associated with tumor development and immunotherapy resistance. This study shows that circFAT1 controls cancer stemness and immune evasion by regulating STAT3 activation. CircFAT1 binds to STAT3 and prevents STAT3 dephosphorylation by SHP1, resulting in the promotion of STAT3 activation. Knockdown of circFAT1 impairs cancer stemness and enhances PD1 blockade immunotherapy.